Does Experience Enhance Cognitive Flexibility? An Overview of the Evidence Provided by the Environmental Enrichment Studies - Gelfo, Francesca (Frontiers in Behavioral Neuroscience, 2019)
Neuroplasticity accounts for the ability of the brain to change in both structure and function in consequence of life experiences. An enhanced stimulation provided by the environment is able to create a form of brain, neural, and cognitive reserve, which allows an individual to cope better with the environmental demands, also in case of neural damage leading to cognitive decline. With its complex manipulation of several stimuli, the animal experimental paradigm of environmental enrichment (EE) appears particularly effective in modulating the ability to successfully respond to the ever-changing characteristics of the environment. According to this point, it could be very relevant to analyze the specific effects of EE on cognitive flexibility (CF). CF could be defined as the ability to effectively change behavior in response to the environmental condition changing. This review is specifically aimed to summarize and focus on the available evidence in relation to the effects of EE on CF. To this aim, findings obtained in behavioral tasks specifically structured to investigate animal CF, such as reversal learning and attentional set-shifting tests (tasks based on the request of responding to a rewarding rule that changes, within one or multiple perceptual dimensions) are reviewed. Evidence provided on the structural and biochemical correlates of these findings are also enumerated. Studies realized in healthy animals and also in pathological models are considered. On the whole, the summarized evidence clearly supports the specific beneficial effects of EE on CF. However, further studies on this key topic are strictly required to gain a comprehensive and detailed framework on the mechanisms by which an enhanced stimulation could improve CF.